2017
DOI: 10.1186/s40623-017-0745-9
|View full text |Cite
|
Sign up to set email alerts
|

Ground-based instruments of the PWING project to investigate dynamics of the inner magnetosphere at subauroral latitudes as a part of the ERG-ground coordinated observation network

Abstract: The plasmas (electrons and ions) in the inner magnetosphere have wide energy ranges from electron volts to megaelectron volts (MeV). These plasmas rotate around the Earth longitudinally due to the gradient and curvature of the geomagnetic field and by the co-rotation motion with timescales from several tens of hours to less than 10 min. They interact with plasma waves at frequencies of mHz to kHz mainly in the equatorial plane of the magnetosphere, obtain energies up to MeV, and are lost into the ionosphere. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
102
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

7
2

Authors

Journals

citations
Cited by 90 publications
(111 citation statements)
references
References 49 publications
2
102
0
Order By: Relevance
“…The coordinated observations by the Arase satellite and the ground-based PWING observation network have allowed more complete study of the origin of intensity modulations less than 1 s in pulsating auroras, which has been an open issue in auroral physics since the 1970s (Royrvik & Davis, 1977). Matsuda et al, 2018;Ozaki et al, 2018) and for aurora at 1/100 s (Shiokawa et al, 2017); see Texts S1 and S2 in the supporting information. Our sampling is for waves at 1/65,536 s (Y.…”
Section: Microscopic Observations Of Pulsating Auroramentioning
confidence: 99%
“…The coordinated observations by the Arase satellite and the ground-based PWING observation network have allowed more complete study of the origin of intensity modulations less than 1 s in pulsating auroras, which has been an open issue in auroral physics since the 1970s (Royrvik & Davis, 1977). Matsuda et al, 2018;Ozaki et al, 2018) and for aurora at 1/100 s (Shiokawa et al, 2017); see Texts S1 and S2 in the supporting information. Our sampling is for waves at 1/65,536 s (Y.…”
Section: Microscopic Observations Of Pulsating Auroramentioning
confidence: 99%
“…The plasma wave experiment (PWE)/waveform capture (WFC) (Kasahara et al 2018b;Matsuda et al 2018) and Software-type wave -particle interaction analyzer (S-WPIA) (Katoh et al 2017;Hikishima et al 2018) have intermittently performed waveform observations along a satellite orbit. Waveform data of plasma waves are important for studying wave-particle interactions through detailed comparisons with the groundbased optical and wave observations (Shiokawa et al 2017). The waveform data would accumulate more than 6 GB if always recorded along a satellite orbit.…”
Section: Introductionmentioning
confidence: 99%
“…The ERG project, therefore, includes both satellite and groundbased observation teams. Ground-based observations are obtained from Super Dual Auroral Radar Network (SuperDARN) high-frequency (HF) radars, European Incoherent Scatter Scientific Association (EISCAT) radar, magnetometers, very low-frequency (VLF)/ELF (extremely low-frequency) loop antennas, riometers, VLF/low-frequency (LF) radio wave receivers, and optical imagers (Shiokawa et al 2017). …”
Section: Introductionmentioning
confidence: 99%
“…In this study, we observed VLF/LF radio waves that are transmitted from several stations in the United States: NDK (25.2 kHz, 46.37°N, 261.47°E, L = 3.0), WWVB (60.0 kHz, 40.67°N, 254.95°E, L = 2.3), and NLK (24.8 kHz, 48.20°N, 238.08°E, L = 2.9). They are received at Athabasca (ATH), Canada (54.6°N, 246.7°E, L = 4.3; Shiokawa et al, ; Tsuchiya et al, ). The amplitude and phase of the transmitter signals are recorded with 0.1‐s time resolution.…”
Section: Instrumentationmentioning
confidence: 99%